All-cellulose-based freestanding porous carbon nanocomposites and their versatile applications. (1st March 2022) - Kong, Xueying; Zhou, Shengyang; Strømme, Maria; Xu, Chao
Abstract: Porous carbons are key functional materials in a range of industrial processes such as gas adsorption and separation, water treatment, and energy conversion and storage. It is, however, important from a sustainability perspective for porous carbons to be synthesized from naturally abundant biopolymers. Nanoengineering of porous carbons using facile binder-free techniques presents significant challenges, but is deemed beneficial for broadening their field of use and improving their application performance. This paper discusses the processing of cellulose-based porous carbons interwoven with cellulose nanofibers to fabricate freestanding nanopapers and aerogels, aiming at developing processable, fully sustainable, and all-cellulose-based carbon nanocomposites. The aerogels, which have cellular networks, low density and high mechanical strength, were investigated as sorbents for CO2 capture and removal of various organics. The presence of rich ultramicropores allows the aerogels to adsorb relatively high amounts of CO2, with high selectivity of CO2 -over-N2 (up to 111). More importantly, the sorbents have high CO2 working capacities and excellent recyclability under temperature swing adsorption conditions. In addition, the aerogels can adsorb various organic solvents remarkably well, corresponding to 100–217 times their own weight. The nanopapers are active photothermal materials that can be applied as solar absorbers for interfacial solar vapor generation, providing a high evaporation rate (1.74 kg m −2  h −1 under one sun illumination). The nanopapers were also employed as electrodes in flexible, foldable supercapacitors with high areal capacitances. This study may provide a basis for further development of and new application areas for all-cellulose-based nanocomposites. Graphical abstract: Image 1 Highlights: All-cellulose-based freestanding porous carbon aerogels and nanopapers were designed. The elastic aerogels were efficient sorbents for CO2 separation and removal of VOCs. The freestanding nanopapers was applied for interfacial solar vapor generation. The freestanding nanopaper electrodes were assembled into flexible supercapacitors.